Immunmodulation in the treatment of dermatological diseases - SEÇKİN GENÇOSMANOĞLU, DİLEK; ÖZGEN, ZÜLEYHA (TURKISH SOC DERMATOLOGY VENEROLOGY, 2013)
Immunological effects have an important role in the action mechanisms of the majority of topical and systemic agents, and even some physical treatment modalities in dermatology. Depending on the disease being treated, these effects may be suppression or stimulation of the immune system as well as modulation of the existing functions. Agents that show their effects mainly by immunmodulation in the treatment of dermatological diseases are discussed in the present article. Treatment alternatives included in the article, azathioprine, mycophenolate mofetil, cyclosporine, glucocorticosteroids, topical calcineurin inhibitors, photo(chemo)therapy, intravenous immunoglobuline, interferon, rituximab, omalizumab, imiquimod and extracorporeal photopheresis are discussed focusing especially on their immunomodulatory effects without any mention on their prescribing details, treatment protocols and monitorization aspects.
Keywords: Immunomodulation; dermatology; treatment; INTRAVENOUS IMMUNOGLOBULIN THERAPY; SKIN MAST-CELLS; ATOPIC-DERMATITIS; IMMUNE GLOBULIN; INDUCED IMMUNOSUPPRESSION; MYCOPHENOLATE-MOFETIL; ULTRAVIOLET-RADIATION; DENDRITIC CELLS; CYCLOSPORINE-A; INTERFERON